Costs and potentials of reducing CO2 emissions in China's transport sector: Findings from an energy system analysis. (1st November 2021) - Du, Huibin; Li, Qun; Liu, Xi; Peng, Binbin; Southworth, Frank
Abstract: As China's transportation system expands it is producing a large amount of end-use emissions. To derive cost-effective measures for CO2 mitigation, the authors of this paper develop a marginal abatement cost (MAC) curve for China's transport sector. Using the TIMES model, MAC curves are derived which identify the linkages among all transport modes, considering, among other uncertainties, the impacts of a carbon peaking policy and driver preferences for plug-in hybrid electric vehicles (PHEVs). The results underline that the intercity passenger transport sector has a cost advantage, with a huge potential for emissions reduction (accounting for almost 38.8% of all CO2 emissions mitigation). The freight sector is another potentially significant contributor to CO2 reduction, underlining its vital role for emission mitigation in the longer run. The carbon peak policy, while making alternative fuel vehicles (AFV) more efficient, is found to increase the overall cost of emissions reduction. A higher ratio of electricity to fossil fuel use by PHEVs drivers would help the transport sector to reduce CO2 much faster. The sensitivity analysis of these and other factors is also estimated in this paper. The final MAC curves provide valuable insights for future low-carbon energy development strategies of China's transport sector. Highlights: MAC curves for the Chinese transport sector using the TIMES model are built. The impacts of a carbon peaking policy and driver preferences for PHEVs are examined. The impacts of discount rates, fuel prices and traffic final demand are identified. The intercity passenger transport sector is a cost-efficient sub-sector for achieving emissions reductions. The large public transport measures and alternative fuel vehicles underline the important role of carbon reduction pathway.